Finding the Connective Tissue in Teacher Education: Creating New Spaces for Professional Learning to Teach - Hopper, Tim; Sanford, Kathy; Fu, Hong (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2016)
A common concern in teacher education programs is the fragmentation of knowledge between courses that contribute to separation between discipline-focused theoretical knowledge and teachers’ practical work in schools. Drawing on reviews on innovative learning spaces in schools and analysis of teacher knowledge, we theorize a conceptualization of professional learning with an intention to draw attention to a re-visualization of teacher education. We refer to the concept of electronic-portfolios as a powerful connective tissue in creating new spaces for teacher education, followed by an outline of an aspect of our teacher education program, with insights from students, that is emerging. We conclude with reflections on how we are integrating deep conceptual understandings of education with cumulative narratives of education in practice.